STUDY ON THE SLOW CRACK GROWTH BEHAVIOR OF PE100 PIPE - DU ZhaoXin; DONG JunHua; GAO BingJun (Jixie qiangdu)
In this article,fatigue crack growth（ FCG） experiments were conducted on cracked round bar（ CRB）specimens manufactured from PE100 pipes at different R-ratios. In addition, these experimental data were employed in extrapolating to the case of creep crack growth（ CCG） on the basis of linear elastic fracture mechanics（ LEFM）. Afterwards,critical crack depth as well as corresponding stress intensity factor for pipes with circumferential crack were determined under service time 50 years.